Field study 6 : on becoming a teacher - Bilbao, Purita P. (Cubao, Philippines : Lorimar Publishing Company Inc., 2010)
FS 6 Workbook aligns the learner's experiences with the National Competency- Based Teacher Standards (NCBTS). The learning experiences embedded in every lesson were intended to create meaningful and rewarding encounters to ensure that the students will feel the joy of teaching and learning. FS 6 is focused on " The Teacher as a person"; " The Teacher's Philosophy of Education"," The Teacher in a School Setting"," The Teacher in the Community"," The Global Teacher" and " The Teacher as a Professional.
Foreword iii -- Preface iv -- Table of Contents vi -- Letter to the Field Student vii -- Letter to the Field Study Teacher viii -- Orientation Notes for Field Study and this Workbook ix -- Approach to Field Study 6 x -- Matrix of Field Study and this Workbook ix -- Suggested Guidelines fof Field Study Students -- Field Study 6 - On becoming A Teacher 1 -- Episode 1 - The Teacher as a person 3 -- Episode 2 - The Teacher's Philosophy of Education 10 -- Episode 3 - The Teacher in Social Setting 17 -- Episode 4 - The Teacher in the Community 23 -- Episode 5 - The Global Teacher as a Professional 44 -- Certificate of Completion of Experential Learning Courses Prescribed by DepEd 53
Keywords: EDUCATION -- PHILIPPINES